Effect of Anisotropy Structure on Plume Entropy and Reactive Mixing in Helical Flows - Ye, Yu; Chiogna, Gabriele; Lu, Chunhui; Rolle, Massimo (Transport in Porous Media, 2018)
Plume dilution and reactive mixing can be considerably enhanced by helical flows occurring in three-dimensional anisotropic porous media. In this study, we perform conservative and reactive transport simulations considering different anisotropy structures of a single inclusion with the objective of exploring the effect of the inclusion’s geometry and orientation on the patterns of twisted streamlines and on the overall dilution and reaction of solute plumes. We analyzed 100 different scenarios by varying key parameters such as the angle of the anisotropic structures with respect to the average flow velocity, the spacing between alternated heterogeneous zones of coarse and fine materials, the permeability contrast between such matrices, and the magnitude of the seepage velocity. Entropy conservation equations and entropy-based metrics for both conservative and reactive species were adopted to quantify dilution, reactive mixing and their interactions with the helical flow patterns in the considered three-dimensional anisotropic setups. The results allowed identifying optimal anisotropic configurations maximizing mixing and reactions, and yielding enhancement factors up to 15 times the outcomes of analogous simulations in homogeneous media. Furthermore, the effects of compound-specific diffusive/dispersive properties of the transported species were found to be relevant for both plume dilution and reactive mixing in helical flows.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Anisotropy; Dilution; Entropy; Helical flow; Reactive mixing